Assetization Turning Things into Assets in Technoscientific Capitalism - Birch, Kean; Muniesa, Fabian (Inside Technology, 2020)
How the asset-anything that can be controlled, traded, and capitalized as a revenue stream-has become the primary basis of technoscientific capitalism. In this book, scholars from a range of disciplines argue that the asset-meaning anything that can be controlled, traded, and capitalized as a revenue stream-has become the primary basis of technoscientific capitalism. An asset can be an object or an experience, a sum of money or a life form, a patent or a bodily function. A process of assetization prevails, imposing investment and return as the key rationale, and overtaking commodification and its speculative logic. Although assets can be bought and sold, the point is to get a durable economic rent from them rather than make a killing on the market. Assetization examines how assets are constructed and how a variety of things can be turned into assets, analyzing the interests, activities, skills, organizations, and relations entangled in this process. The contributors consider the assetization of knowledge, including patents, personal data, and biomedical innovation; of infrastructure, including railways and energy; of nature, including mineral deposits, agricultural seeds, and "natural capital"; and of publics, including such public goods as higher education and "monetizable social ills." Taken together, the chapters show the usefulness of assetization as an analytical tool and as an element in the critique of capitalism. Contributors Thomas Beauvisage, Kean Birch, Veit Braun, Natalia Buier, Béatrice Cointe, Paul Robert Gilbert, Hyo Yoon Kang, Les Levidow, Kevin Mellet, Sveta Milyaeva, Fabian Muniesa, Alain Nadaï, Daniel Neyland, Victor Roy, James W. Williams